Cr–Zn Redox Battery with NiFe2O4 as Catalyst for Enhanced Degradation of Cr(VI) Pollution - Luo, T.; Wang, S.; Hou, X.; Chen, F.; Liu, X.; Shao, Zongping; Yan, H. (American Chemical Society, 2019)
A novel Cr-Zn redox battery, which consists of K2Cr2O7 acid solution as cathode and metal zinc as anode, has been introduced to degrade Cr(VI) pollution and obtain electric energy. During the redox reaction, Cr(VI) is degraded into Cr(III) while electric energy is generated on external circuits. In order to increase the output energy density of this redox battery, NiFe2O4 (NFO) is introduced as catalyst for degradation of Cr(VI). The electrochemistry performances are recorded. When NFO is applied as catalyst, the output energy reaches 2660 Wh kg-1 with a discharge plateau at 1.50 V during the Cr(VI) degradation process when the battery is discharged under a current of 1 mA. Moreover, the NFO catalyst helps to stable the output power density when the discharge current rises. Besides, the degradation ratio of Cr(VI) can achieve almost 100% after the redox battery is fully discharged. This result is superior to many of the current Cr(VI) removal/degradation methods.